Adjustable wide multifunctional trolley / Muhammad Saiful Aiman Mohd Zin and Ab Aziz Mohd Yusof - Mohd Zin, Muhammad Saiful Aiman; Mohd Yusof, Ab Aziz (School of Mechanical Engineering, 2023)
The project focuses on addressing the shortcomings of commonly used trolleys in various industries. While trolleys serve the purpose of transporting materials, they are often not user-friendly and can result in back pain and potential harm to the user's spine. To tackle this issue, a new trolley design has been developed that offers multiple functions while preventing back pain during lifting and loading activities. The main objectives of this project are to design an adjustable, wide, and multifunctional trolley, as well as analyze and fabricate an extendable version of this trolley. The target audience for this project includes individuals of all ages, including women, senior citizens, and children, ensuring that everyone can easily handle this machine. The new trolley design aims to alleviate users' concerns about back pain, allowing them to work more comfortably. During the fabrication process, careful consideration is given to selecting appropriate materials that are lightweight, durable, and capable of withstanding heavy loads. Ultimately, this project aims to introduce a new and versatile trolley product with enhanced functionality